2011
DOI: 10.1111/j.1365-2834.2011.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and challenges in the management of maternity care for migrant women

Abstract: The Norwegian model for managing cultural diversity in maternity care needs to be developed. Capacity building and a closer cooperation between maternity care services is necessary. IMPLICATIONS FOR MIDWIVES AND NURSING MANAGEMENT: Maternity care requires reflection at several levels to reduce disparities in individual health. In order to ensure continuity and a trusting relationship, it is necessary to organize leadership and adopt flexible models that support migrant women's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 17 publications
0
62
0
1
Order By: Relevance
“…It has been found in qualitative studies that there are subgroups among immigrant women who are vulnerable and that the flexibility of maternity services should be improved in order to better meet their specific needs [19, 20]. A recent Norwegian registry study showed that, among the compared groups, the risk of adverse obstetric outcomes was higher among women of African and Asian descent [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found in qualitative studies that there are subgroups among immigrant women who are vulnerable and that the flexibility of maternity services should be improved in order to better meet their specific needs [19, 20]. A recent Norwegian registry study showed that, among the compared groups, the risk of adverse obstetric outcomes was higher among women of African and Asian descent [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence in the articles, it is acknowledged that the migrant women's situation in a new country is related to lack of 'communication and connection' to others (Lyberg et al 2012). Their situation can be explained by the diversity in experiences of security, knowledge, and personal values.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we proceeded to the identification of a preliminary framework reflecting participants’ perspectives as well as theoretical discussions on the topic [2224, 26, 30, 3234, 41]. We used this analytic structure for indexing the data , a procedure most commonly referred to as coding (e.g., [42]).…”
Section: Methodsmentioning
confidence: 99%
“…Some health care professionals, guided by the perceptions they have of their patients, may use the power associated with their position to revindicate certain values that contribute to health care inequities [27, 3234], creating a distance between “us” and “them” (i.e., their patients) [35]. …”
Section: Introductionmentioning
confidence: 99%